1996
DOI: 10.1007/bf01591364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection in pregnant Turkish women and their families

Abstract: A total of 5,366 pregnant Turkish women were screened for hepatitis B surface antigen (HBsAg) and 225 (4.2%) of them were found to be positive. Hepatitis B e antigen (HBeAg) was detected in 6.2% of HBsAg-positive pregnant women. the overall prevalence of HBsAg and antibody to HBsAg (anti-HBs) among the spouses, previous children, mothers and first degree relatives of the HBsAg-positive pregnant women was 56%, 49%, 79% and 74% respectively. The prevalence of HBsAg is thus high in pregnant Turkish women with fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
0
8
0
3
Order By: Relevance
“…One out of the 1000 pregnant women was found positive for HBeAg. Higher prevalence has been reported in pregnant women: 4.6% in South Africa 14 , 6.2% in Turkey 13 and 43% in Taiwan Group IV (n = 98) . Of special interest is the group of 20 anti-HBc positive women with 'isolated anti-HBc'.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…One out of the 1000 pregnant women was found positive for HBeAg. Higher prevalence has been reported in pregnant women: 4.6% in South Africa 14 , 6.2% in Turkey 13 and 43% in Taiwan Group IV (n = 98) . Of special interest is the group of 20 anti-HBc positive women with 'isolated anti-HBc'.…”
Section: Discussionmentioning
confidence: 86%
“…Similar results were reported by other investigators 10 . In other parts of the world, the prevalence of HBsAg in pregnant women has been reported as 0.1-39.7% [10][11][12][13] . One out of the 1000 pregnant women was found positive for HBeAg.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal population, a HBsAg positivity of 3.4 and 14% was reported from Izmir in 1995 and from Gaziantep in 1996, respectively [1]. A study of pregnant women in 1995 reported the HBsAg prevalence to be 4.2% [5]. It is accepted that in Turkey, the rate of HBsAg positivity, based on the use of the ELISA method, is between 3.9 and 12.5% [1].…”
Section: Discussionmentioning
confidence: 99%
“…'nın yaptığı çalışmada; hastane personelinde %5,41, normal populasyonda %5,0 pozitiflik saptanmıştır (33). Ülkemizde sağlık personeline yönelik yapılan diğer çalışmalarda HBsAg pozitifliği 1,9-4,1% arasında bulunmuştur (14,(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionunclassified